2013
DOI: 10.1159/000350741
|View full text |Cite
|
Sign up to set email alerts
|

The rs9939609 Polymorphism in the <b><i>FTO</i></b> Gene Is Associated with Fat and Fiber Intakes in Patients with Type 2 Diabetes

Abstract: Background/Aims: The common polymorphism in the FTO gene (rs9939609) has been associated with obesity, type 2 diabetes, and appetite regulation. The aim of this study was to evaluate possible associations of FTO rs9939609 with dietary factors in patients with type 2 diabetes. Methods: This was a cross-sectional study of 236 patients with type 2 diabetes (age 60.0 ± 10.3 years; diabetes duration 12.7 ± 8.2 years; 53.4% females) who were genotyped for FTO rs9939609. Patients underwent clinical and laboratory eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 70 publications
1
23
0
3
Order By: Relevance
“…Timpson et al also found that carriers of the minor variants of rs9939609 consumed more fat and total energy than those non-carriers [47]. Recently, further evidence has suggested that FTO interacts with energy intake patterns in children, as related to obesity risk [64][68]. The findings of this study showed that the genetic variation of rs9939609 was associated with a meat-based dietary preference, and children with the A allele were predisposed to prefer a meat-based diet, which is characterized by higher energy density, higher fat, and lower dietary fiber than either plant-based or balanced diets.…”
Section: Discussionmentioning
confidence: 99%
“…Timpson et al also found that carriers of the minor variants of rs9939609 consumed more fat and total energy than those non-carriers [47]. Recently, further evidence has suggested that FTO interacts with energy intake patterns in children, as related to obesity risk [64][68]. The findings of this study showed that the genetic variation of rs9939609 was associated with a meat-based dietary preference, and children with the A allele were predisposed to prefer a meat-based diet, which is characterized by higher energy density, higher fat, and lower dietary fiber than either plant-based or balanced diets.…”
Section: Discussionmentioning
confidence: 99%
“…Ortega-Azorín et al (2012) found a significant gene-diet interaction of the FTO rs9939609 and MC4R rs17782313 polymorphisms with type 2 diabetes depending on diet, in which the Mediterranean diet counteracts the genetic predisposition. A cross-sectional study found that individuals carrying both AA risk allele of the rs9939609 polymorphism were positively associated with a high intake of total fat (>34% energy) and low fiber consumption (<16 g/day), independently of BMI (Steemburgo et al 2013). It has also been reported in a recent study that obesity susceptibility genes (FAIM2, FLJ35779, FTO, LRRN6C, RBJ, and SEC16B) were found to interact with dietary carbohydrates (sugar-sweetened beverages) to increase BMI when one or more servings are consumed per day (Qi et al 2012).…”
Section: Preventionmentioning
confidence: 99%
“…However, Steemburgo et al . reported that carriers of the AA genotype of the FTO rs9939609 had an increased fat and decreased fibre consumption, independent of BMI. It should be noted, however, that the participants in their study were diabetic, whereas the participants in the present study were healthy individuals with blood glucose levels (<5.6 mmol L −1 ) .…”
Section: Discussionmentioning
confidence: 99%